An intermedial perspective for ekphrasis: How photographs contribute to writing about artists - Lunyova, Tetyana (Cognition, Communication, Discourse, 2024)
This paper examines the relationships that emerge in the process of meaning-making in the anthology Writers on artists (Minton, 2001) between photographic portraits of the artists and other images and verbal textual components. The findings demonstrate that as indexes, the photographs of the artists testify to the artists’ real existence; as icons, these photographs contribute to the representation of the artists’ uniqueness. Through these two roles, the artists’ photographic portraits ensure the status of the ekphrasis in the essays as “actual ekphrasis” (in Hollander’s terms). In interaction with the biographical notes, the photographs of the artists highlight their uniqueness. As elements in the multimodal complexes “artist’s photo & artist’s bio”, the artists’ photographs enter into the relationships of similarity and contrast with the writers’ photographs in the multimodal complexes “writer’s photo & writer’s bio”, which are instrumental in creating symbolic dialogic space for the discussion of the works of the visual arts in the essays. Those photographs that are photographs of the artists’ painted or drawn portraits rather than people themselves establish strong semantic links with descriptive ekphrasis. Some of the objects captured in the artists’ photographs can contribute to descriptive ekphrasis. Those photographic portraits that offer psychological characterization of the artists work in synchrony with interpretative ekphrasis. The photographs that can symbolically evoke schemata of knowledge which have high relevance for ekphrastic interpretations and metaekphrastic discussions strongly support meanings generated in the essays. The photographs that are likely to be interpreted symbolically contribute most significantly to the meaning-making in the essays.